Le crédit, outil d’inclusion sociale : le cas de Valente (Bahia) - Pauline Bensoussan (Cahiers des Amériques Latines, 2010)
Long-time neglected from public policy and excluded from traditional financial institutions, small rural producers in the sertão baiano are facing harsh climate conditions (semi-arid) and social or economic contingencies. Since the 1980’s, civil society actors (associations, cooperatives) have been coordinating innovative social and economic alternatives in order to create added value to human and natural resources. The State has though been only rarely involved in this process. This study, based on an extensive field work, highlights the forces that have led to the emerging dynamics in the sisal territory. The analysis refers to the historical process of social mobilization and to the definition of a rural project that has developed opportunities for small producers to enlarge their choices and independency. The aim to achieving financial integration of these producers has led to the creation of the rural credit cooperative of Valente in 1993, which aims to facilitate access to credit by offering services adapted to the financial needs of the producers and accompanying devices. In this sense, it refers to microfinance practices and to the fight against poverty.